A Hakka Woman's Singapore Stories - Lee Wei Ling
Dr Lee Wei Ling, scion of Singapore$1 (Bs first family, writes about her life as a daughter, doctor and diehard Singaporean. This book addresses a range of matters affecting Singaporeans in a personal way. It reflects her personality, profession, relationships, passions and perspective of life, Singapore and the world, and her loved ones. The chapters are grouped thematically and are capped by an epilogue of six articles which encapsulate the two events that had a major impact on the writer, and resonated deeply with Singaporeans: the passing of her parents.s